The role of CRISPR‐Cas in advancing precision periodontics. (16th January 2021) - Barbour, Abdelahhad; Glogauer, Judah; Grinfeld, Lis; Ostadsharif Memar, Rouzbeh; Fine, Noah; Tenenbaum, Howard; Glogauer, Michael
Abstract: The significant advancement of molecular biology has revolutionized medicine and provided important technologies to further clinical research development. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) are DNA sequences derived from bacteriophages which have previously infected the bacterial species. The CRISPR–Cas system plays a key role in bacterial defense by detecting and destroying DNA fragments during subsequent bacteriophage invasions. The Cas9 enzyme recognizes and cleaves new invading CRISPR‐complementary DNA sequences. Researchers have taken advantage of this biological device to manipulate microbes' genes and develop novel therapeutics to tackle systemic disease. In this review, we discuss the potential of utilizing CRISPR–Cas systems in the periodontal field to develop personalized periodontal care. We summarize promising attempts to bring this technology to the clinical setting. Finally, we provide insights regarding future developments to best utilize the CRISPR–Cas systems to advance precision periodontics. Although further research is imperative to evaluate the safety and potential of using CRISPR–Cas to develop precision periodontics approaches, few studies showed promising data to support the investment into this important technology in the dental sector. CRISPR–Cas9 can be a useful tool to create knockouts in vitro and in vivo as a screening tool to identify cellular pathways involved in the pathogenesis of periodontitis. Alternative CRISPR systems such as CRISPRa, CRISPRi, and Cas13 can be used to modify the transcriptome and gene expression of genes involved in periodontitis progression. CRISPR systems such as Cas3 can be used to target the periodontal biofilm and to develop new strategies to reduce or eliminate periodontal pathogens. Currently, the utility of CRISPR–Cas applications in clinical settings is limited. Through this review, we hope to foster further discussion in the periodontal research and clinical communities with respect to the potential clinical application of novel, CRISPR–Cas based, therapeutics for periodontitis.